2004
DOI: 10.1590/s0100-879x2004000800003
|View full text |Cite
|
Sign up to set email alerts
|

Patterns of intracellular cytokines in CD4 and CD8 T cells from patients with mycobacterial infections

Abstract: Using a short-term bulk culture protocol designed for an intracellularstaining method based on a flow cytometry approach to the frequencies of cytokine-producing cells from tuberculosis and leprosy patients, we found distinct patterns of T cell subset expression. The method also reveals the profile of peak cytokine production and can provide simultaneous information about the phenotype of cytokineproducing cells, providing a reliable assay for monitoring the immunity of these patients. The immune response of M… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
13
0

Year Published

2006
2006
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 28 publications
(13 citation statements)
references
References 27 publications
(50 reference statements)
0
13
0
Order By: Relevance
“…These results are in contrast to those assessing the potential of CFC for the diagnosis of M. tuberculosis infection. In a number of such studies where cells were stimulated with PPD, it was not possible to distinguish BCG-vaccinated patients from TB patients (1,16,33,34). Accurate diagnosis was observed only where ESAT-6 was used as the stimulating antigen, and an overall sensitivity of between 90 and 95% was achieved.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…These results are in contrast to those assessing the potential of CFC for the diagnosis of M. tuberculosis infection. In a number of such studies where cells were stimulated with PPD, it was not possible to distinguish BCG-vaccinated patients from TB patients (1,16,33,34). Accurate diagnosis was observed only where ESAT-6 was used as the stimulating antigen, and an overall sensitivity of between 90 and 95% was achieved.…”
Section: Discussionmentioning
confidence: 99%
“…Accurate diagnosis was observed only where ESAT-6 was used as the stimulating antigen, and an overall sensitivity of between 90 and 95% was achieved. The number of responding CD4 ϩ T cells ranged from 0.1 to approximately 1%, although overall responses to ESAT-6 were very low (1,16,33,34). Although ESAT-6 has been suggested as a potential diagnostic tool for distinguishing M. bovis-infected cattle from BCG-vaccinated animals, it is clear that only a proportion of infected animals respond to this antigen (15).…”
Section: Discussionmentioning
confidence: 99%
“…Additionally, TNF-␣ plays a critical role in immunity to C. neoformans (35,36). However, similar functional distinctions in T cells have been reported in other infections (37,38). In the CD8 ϩ T cell response to Listeria monocytogenes, intracellular cytokine staining for IFN-␥ detects higher frequencies of tetramer positive (Ag specific) cells than TNF-␣ (39).…”
Section: Discussionmentioning
confidence: 65%
“…Usually the peripheral profile of cytokines in leprosy (serum and plasma) reflects the measure of many sources of cytokine production 17,18 without identifying which specific cell is really compromised 19,20 . It has been observed that PBMCs present different levels of proliferation index of cytokines when they are stimulated in vitro with Mycobacterium leprae extracts [21][22][23] .…”
Section: A B C D Discussionmentioning
confidence: 99%